The persistent global disparities in environmental and climate communication scholarship - Bera, Sohinee; Vilchez, Amanda; Muenster, Roxana M. (Frontiers in Communication, 2025)
IntroductionAs the climate crisis progresses, it is clear that environmental catastrophes are unequally distributed and unequally caused. The Global South is disproportionately affected by the consequences of climate change despite being less responsible for some of its anthropogenic causes, compared to the Global North.MethodsTo understand whether environmental and climate communication scholarship reflect the global nature of these crises, we conducted a publication review of 505 articles published in the top-producing journals of climate communication between 2020 and 2022, along with an authorship survey and keyword network analysis. We investigate who conducts environmental and climate communication research, the geographic focus and contextualization of the research, and the thematic focus of the research.ResultsThe Global North dominates in authorship (93%) and research focus (67%), while the Global South affiliated authors make up a fraction of the sample (7%) and of the research focus (12%), revealing a gap in scholarship based in and about the Global South. While articles across the Global North and the Global South focused on climate change and adaptation, articles about the Global South more prominently focused on disasters, vulnerability, and risk management.ConclusionThe review highlights the need for greater diversity in environmental and climate communication publishing and suggests consistent geographic naming practices in titles to achieve a more inclusive academy.